Long-lived hypopituitary Ames dwarf mice are resistant to the detrimental effects of high-fat diet on metabolic function and energy expenditure - Hill, Cristal M. (2016)
Growth hormone (GH) signaling stimulates the production of IGF-1; however, increased GH signaling may induce insulin resistance and can reduce life expectancy in both mice and humans. Interestingly, disruption of GH signaling by reducing plasma GH levels significantly improves health span and extends lifespan in mice, as observed in Ames dwarf mice. In addition, these mice have increased adiposity, yet are more insulin sensitive compared to control mice. Metabolic stressors such as high-fat diet (HFD) promote obesity and may alter longevity through the GH signaling pathway. Therefore, our objective was to investigate the effects of a HFD (metabolic stressor) on genetic mechanisms that regulate metabolism during aging. We show that Ames dwarf mice fed HFD for 12 weeks had an increase in subcutaneous and visceral adiposity as a result of diet-induced obesity, yet are more insulin sensitive and have higher levels of adiponectin compared to control mice fed HFD. Furthermore, energy expenditure was higher in Ames dwarf mice fed HFD than in control mice fed HFD. Additionally, we show that transplant of epididymal white adipose tissue (eWAT) from Ames dwarf mice fed HFD into control mice fed HFD improves their insulin sensitivity. We conclude that Ames dwarf mice are resistant to the detrimental metabolic effects of HFD and that visceral adipose tissue of Ames dwarf mice improves insulin sensitivity in control mice fed HFD.